Common CYP2D6, CYP2C9, and CYP2C19 Gene Variants, Health Anxiety, and Neuroticism Are Not Associated With Self-Reported Antidepressant Side Effects - Maggo, Simran; Kennedy, Martin A.; Barczyk, Zoe A.; Miller, Allison L.; Rucklidge, Julia J.; Mulder, Roger T.; Foulds, James A. (Frontiers in Genetics, 2019)
Many patients prescribed an antidepressant stop taking it because of side effects. Genetic factors and psychological factors including state or trait anxiety, may explain variation in side effect outcomes. Our aim was to examine the relative contribution of genetic and psychological factors in people with self-reported antidepressant side effects. We undertook a case control study (n=194) of people who took a selective serotonin reuptake inhibitor (SSRI) or serotonin / noradrenaline reuptake inhibitor (SNRI) in the past two years, recruited via social media advertising. Cases had previously not tolerated at least one trial of an SSRI or SNRI, evidenced by stopping the drug or reducing the dose by at least 50% because of a side effect. Control participants had taken an SSRI or SNRI but did not meet case criteria. Variation in the genes CYP2D6, CYP2C19 and CYP2C9 was analyzed by Sanger sequencing on DNA extracted from blood or saliva. Participants completed the Short Health Anxiety Inventory-18, K10 and NEO-FFI-3 personality questionnaire. Participants were (87.1%) female. 70.8% had a current K10 score of 22 or more. There was no consistent evidence that cases had higher psychological distress, health anxiety or neuroticism. There was low correspondence between participants’ CYP2D6, CYP2C19 and CYP2C9 phenotypes and their history of antidepressant tolerability. For this cohort of patients a history of not tolerating SSRI or SNRI therapy was not associated with variation in the pharmacogenes we tested, nor was it associated with health anxiety or neuroticism.